Leadership Practices on Employee Performance at PT Dame Alam Sejahtera - Sitompul, Sindia Olesen; Munthe, Rusli Ginting (Growth: Journal Management and Business, 2025)
This study aims to determine the influence of leadership on employee performance at PT Dame Alam Sejahtera, a hazardous waste management company based in Karawang. The research was motivated by suboptimal employee performance, indicated by low productivity, lack of motivation, and ineffective workplace communication. A quantitative approach with a descriptive-correlational research design was employed, using a simple linear regression analysis technique. A total of 32 respondents were selected through purposive sampling from a population of 35 employees. Data were collected using questionnaires that had been tested for validity and reliability. The results revealed a significant influence of leadership on employee performance. These findings imply that effective leadership characterized by clear direction, support, and appreciation can enhance employee motivation and overall performance. The study underscores the importance of leadership in fostering a productive and sustainable work environment, and contributes to the literature by providing empirical evidence on the role of leadership in enhancing employee performance within high-risk industrial contexts such as hazardous waste management.